Palestine and Israel War Conflict During COVID-19 - Martadinata, Ilham; Gibran, Muhamad Noor; Kaunang, Elfira Sylviani; Hadianto, Muhammad; Risman, Helda (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to determine how international law affects the Israeli-Palestinian conflict during the COVID-19 pandemic. The approach used in this research is literature study, which entails gathering pertinent material from books and journals, evaluating it, and drawing conclusions. Concerns regarding the socio-economic circumstances of Palestinians have been highlighted by the fast-spreading COVID-19 epidemic. Overcoming two issues at once is becoming more and more difficult. Considering the harm done to infrastructure for sanitation, hygiene, and water, the Palestinians’ situation is getting better. The COVID-19 virus is being stopped by impeding the flow of essential supplies into the Palestinian state and causing environmental harm, both of which may affect public health. International humanitarian law is in place to prevent these kinds of tragedies, but the Israeli government and military disobey these laws. From an international law standpoint, this research helps understand how the state of Israel behaved toward Palestine during the COVID-19 epidemic. References to a wide range of national and international periodicals and books were used in the preparation of this research. In addition, it makes use of the most recent news about the subjects covered. The findings of this review of the literature indicate that despite an increase in attacks on Palestinian civilians, the situation between Israel and Palestine has not improved